Process independent automated sizing methodology for current steering DAC - Vural, R. A.; Kahraman, N.; Erkmen, B.; Yildirim, T. (TAYLOR & FRANCIS LTD, 2015)
This study introduces a process independent automated sizing methodology based on general regression neural network (GRNN) for current steering complementary metal-oxide semiconductor (CMOS) digital-to-analog converter (DAC) circuit. The aim is to utilise circuit structures designed with previous process technologies and to synthesise circuit structures for novel process technologies in contrast to other modelling researches that consider a particular process technology. The simulations were performed using ON SEMI 1.5 mu m, ON SEMI 0.5 mu m and TSMC 0.35 mu m technology process parameters. Eventually, a high-dimensional database was developed consisting of transistor sizes of DAC designs and corresponded static specification errors obtained from simulation results. The key point is that the GRNN was trained with the data set including the simulation results of ON-SEMI 1.5 mu m and 0.5 mu m technology parameters and the test data were constituted with only the simulation results of TSMC 0.35 mu m technology parameters that had not been applied to GRNN for training beforehand. The proposed methodology provides the channel lengths and widths of all transistors for a newer technology when the designer sets the numeric values of DAC static output specifications as Differential Non-linearity error, Integral Non-linearity error, monotonicity and gain error as the inputs of the network.
Keywords: neural networks; digital-to-analog converter; static characterisation; transistor sizing; modelling; ANALOG; DESIGN; CMOS; NETWORKS; MODEL; Engineering